2008
DOI: 10.1021/jp803812p
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Adsorption Effect on Silica Surface Electrostatic Patterning

Abstract: This work verifies a model for the creation and dissipation of reproducible electric potential patterns on silica surfaces, based on water adsorption, ionization, and ion migration under applied electric potential. Samples were thin silica films grown on silicon wafers and partially covered with sets of parallel gold stripe interdigitated electrodes that are normally used for Kelvin force microscope calibration. Noncontact electric potential measurements with a 20 nm spatial resolution were done using the Kelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 48 publications
2
57
0
2
Order By: Relevance
“…However, extracting the magnitude of the capillary force from the pull-off force requires assuming that the other intersurface forces, e.g., electrostatic or hydration forces, are either constant or unimportant, which may not always be justified. 22,23 As well, the pull-off force may be governed by multiple hysteretic processes that are not easily distinguished. In ultrahigh vacuum (UHV), adhesion hysteresis can arise from charge transfer from triboelectrification, plastic deformation, material transfer, differences in work function, contact angle hysteresis in solidÀsolid wetting, and induced molecular vibrations (beating) of the solid surfaces.…”
Section: ' Introductionmentioning
confidence: 99%
“…However, extracting the magnitude of the capillary force from the pull-off force requires assuming that the other intersurface forces, e.g., electrostatic or hydration forces, are either constant or unimportant, which may not always be justified. 22,23 As well, the pull-off force may be governed by multiple hysteretic processes that are not easily distinguished. In ultrahigh vacuum (UHV), adhesion hysteresis can arise from charge transfer from triboelectrification, plastic deformation, material transfer, differences in work function, contact angle hysteresis in solidÀsolid wetting, and induced molecular vibrations (beating) of the solid surfaces.…”
Section: ' Introductionmentioning
confidence: 99%
“…This may be attributed to the heterogeneous surface properties of silica. It is reported that the surface potential of dielectric surfaces is heterogeneous [16,17,33]. Surface roughness may be another contributor to the variation because the silica surface also has a surface roughness of about 2 nm in RMS (root mean square), whereas mica is atomically flat [21].…”
Section: Total Adhesive Forcementioning
confidence: 99%
“…It is unclear what led to this result, but the heterogeneity of silica including surface roughness and electrostatic charge can be a possible reason it is difficult to reproduce or predict the surface potential of insulating materials [16].…”
Section: Total Adhesive Forcementioning
confidence: 99%
See 1 more Smart Citation
“…47 Posteriormente 48 foram analisadas superfícies não cristalinas de sílica de Stöber (Figura 3), sendo observado que o seu potencial elé-trico é modificado quando se muda a umidade, dentro de um ambiente completamente isolado eletricamente e aterrado (Figura 4). Esse resultado é particularmente interessante, pois mostra a eletrização de isolantes muito bem protegidos da ação de campos externos, ao mesmo tempo em que vincula a eletrização com adsorção de vapor de água.…”
Section: Figura 1 Imagens De Efm E Kfm De Alguns Polímeros Regiões unclassified